Self-Efficacy, Work Environment, and Discipline Boost Job Satisfaction in Indonesia - Alif Maulana Rahmatullah; Vera Firdaus (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines how self-efficacy, work environment, and work discipline affect job satisfaction at PT. Sinaraya Nugraha Ahmadaris Medika. Using a quantitative, descriptive approach, the research sampled 117 employees from a population of 166 through proportional random sampling. Data collection involved observation, interviews, and questionnaires, and analysis was performed using multiple linear regression with SPSS version 22. The results indicate that self-efficacy, work environment, and work discipline each have a positive and significant impact on job satisfaction. These findings suggest that improving these factors can enhance employee satisfaction and potentially boost organizational performance. Highlight: Self-efficacy positively impacts job satisfaction. Better work environments increase job satisfaction. Strong work discipline boosts job satisfaction. Keyword: self-efficacy, work environment, work discipline, job satisfaction, quantitative research